9^1/3 * 3^x = 27^4/5
Rewrite 9 as 3^2
(3^2)^1/3 * 3^x = 27^4/5
Multiply the exponents in the first term:
3^2/3 * 3^x = 27^4/5
Use power rule to combine exponents:
3^(2/3 +x) = 27^4/5
Rewrite the 2nd term:
3^(2/3 +x) = (3^3)^4/5
Set the exponents only to equal:
2/3 + x = 3(4/5)
Solve for x:
simplify the right side:
2/3 + x = 12/5
Subtract 2/3 from both sides:
x = 26/15
The probability that her first treat is jelly is 4/20. Since she eats the candy and does not replace it, the probability the second treat is jelly would be 3/19 (1 less jelly and 1 less total candies). You would then multiply (4/20) by (3/19). That is your answer.
Answer:
Incorrect
Step-by-step explanation:
The fraction of 6/12 all squared gives 36/144 36/36 and 144/36 reduces to 1/4.
Second one
1/16
3/8 divided by 1/6=1/16